Magnesium and manganese induced changes on chemical, nutritional, antioxidant and antimicrobial properties of the pansy and Viola edible flowers - de Oliveira, Izamara; Chrysargyris, Antonios; Finimundy, Tiane C.; Carocho, Márcio; Santos-Buelga, Celestino; Calhelha, Ricardo C.; Tzortzakis, Nikos G.; Barros, Lillian; Heleno, Sandrina A (My University, 2024)
Pansy and viola edible flowers were grown hydroponically with different levels of Mg and Mn. The nutritional composition was determined using standard methods. Free sugars, fatty acids, organic acids, tocopherols, and phenolic compounds were analyzed using various HPLC and GC devises. The extract's antimicrobial, antioxidant, cytotoxicity, and anti-inflammatory activity were assessed. The results indicated that Mg enrichment negatively affected plant growth and mineral accumulation but improved photosynthetic performance. The edible flowers contained significant amounts of protein, low levels of fat, and varying sugar contents, such as glucose and fructose. Various fatty acids and phenolic compounds were identified, with different concentrations depending on the treatment. The flowers exhibited antioxidant potential, antimicrobial activity, cytotoxic effects, and anti-inflammatory properties. The correlations between the investigated parameters not only expand knowledge on Mg and Mn interaction but also catalyze significant advancements in sustainable agriculture and food health, fostering a healthier and more conscious future.
Keywords: Phenolic compounds; Bioactivity; Biocidal activity; Hydroponics; Mineral antagonism; Nutritional profile